A Requirement Model For Baghdad University's E-Magazine System For Scientific Research - Faieq, Alaa. K. (2008)
In this study noticed that magazine face difficulties in retrieving researcher and Evaluator data because they are working manually; these difficulties and problems can be summarized in organizing and managing appointments, Researcher's records, and Evaluator issues. Where are designed and implemented a computerized system to solve these problems and help manager doing their jobs in a better way. This system will improve the performance of managing all tasks in the Baghdad university magazine that it will save time and keeps and retrieve data easily and perfectly. In addition to that, the data will be more accurate, secure, and safe.